Centros-que-têm-periferias e periferias-que-têm-centros: Raúl Prebisch - Mallorquin, Carlos (Revista USP, 2023)
The first part of this text questions the hegemonic idea in Latin America and Europ e regarding Prebisch’s stance on paternity and the role that industrialization should have, an aspect that has inhibited historians from observing the cautious stance that the Argentine presents in this regard. Next, a critique will be made of the concept of surplus that forms part of the evolution of Prebisch’s thought from the early 1970s onwards. Since Prebisch resolved this theoretical-political aspect between 1945 and 1949. The vocabulary around structural heterogeneity, advocated throughout the book Capitalismo periférico – crisis y transformación (1981), exceeds the sections dedicated to the distributive struggle developed through that concept of surplus.